Randomized benchmarking for qudit Clifford gates. (15th June 2020) - Jafarzadeh, Mahnaz; Wu, Ya-Dong; Sanders, Yuval R; Sanders, Barry C
Abstract: We introduce unitary-gate randomized benchmarking (URB) for qudit gates by extending single- and multi-qubit URB to single- and multi-qudit gates. Specifically, we develop a qudit URB procedure that exploits unitary 2-designs. Furthermore, we show that our URB procedure is not simply extracted from the multi-qubit case by equating qudit URB to URB of the symmetric multi-qubit subspace. Our qudit URB is elucidated by using pseudocode, which facilitates incorporating into benchmarking applications.